Research on the Influence of Characteristics of the Annular Connecting Pipe on the Transmission Loss of the Expanded Exhaust Muffler - Yue Cheng; Wenhua Yuan; Jun Fu; Yi Ma; Wei Zheng (Shock and Vibration)
In order to broaden the muffler frequency band in the low-frequency range of the exhaust muffler and to achieve the purpose of broadband noise reduction, in this paper, a model of an annular connecting pipe muffler is proposed using the finite element method (FEM) to simulate the nonreflection boundary condition and to solve the transmission loss (TL). In addition, the experimental value is obtained by the spatial five-point measurement method and compared with the simulated value, and the validity and reliability of the solution model are verified. Compared with a simple expansion muffler, the average TL of the annular connecting pipe muffler is increased by 11.86 dB, and the maximum TL is increased by 18.31 dB, effectively widening the muffler frequency area, and the overall performance is effectively improved. Finally, the influence of structural factors is analyzed, including the width (W) of the annular connecting pipe, the length (L) of the annular connecting pipe, and the length ratio (m) of the front and rear chambers on the TL and on the width of the anechoic frequency band. The results reveal that the width and length of the annular connecting pipe and front-to-back cavity length ratio are the most significant factors to influence the TL, muffler frequency band, and elimination or reduction of the passing frequency, respectively.